Alexandre Heberte: inspirações para tecer a vida em sala de aula - Perches, Katherine [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
With the theme "Alexandre Heberte: inspirations to weave life in the classroom.", the current research seeks to investigate the artist's work expressed in the title, relating weaving to the experiences of those who produce it, highlighting its potential as a proposal for the classroom. As a general objective, it seeks to analyze Alexandre Heberte's artistic weaving production and how this manual work can tell life trajectories, how the plots are permeated by the baggage of those who make it, creating, in the end, a workshop based on the research carried out. It is a research in art education involving a triangular proposal by Ana Mae Barbosa, which seeks to emphasize the appreciation of this ancestral and contemporary doing within the classroom.

Tendo como tema “Alexandre Heberte: inspirações para tecer a vida em sala de aula”, a atual pesquisa busca investigar o trabalho do artista mencionado no título, relacionando a tecelagem com as vivências de quem a produz, ressaltando sua potencialidade como proposta para sala de aula. Como objetivo geral, busca analisar a produção em tecelagem artística de Alexandre Heberte e como esse trabalho manual pode contar trajetórias de vida, de como as tramas são permeadas por bagagens de quem as faz, criando, ao final, uma oficina com base na pesquisa realizada. É uma pesquisa em arte-educação, envolvendo a proposta triangular de Ana Mae Barbosa, que busca ressaltar a valorização desse fazer ancestral e contemporâneo dentro da sala de aula.
Alexandre Heberte: inspirations to weave life in the classroom
Keywords: Weaving; Contemporary textile art; Life trajectories; Alexandre Heberte; Tecelagem; Arte têxtil contemporânea; Trajetórias de vida